Antimicrobial Resistance of Nosocomial Infections in Children - Herry Garna (Paediatrica Indonesiana, 1993)
A 9 month prospective study , from August 1988 to April 1989, was performed at the Department of Child Health, Medical School, Padjadjaran University, Hasan Sadikin Hospital Bandung. The aim of the study was to identify the pattern of sensitivity of bacteria causing nosocomial infections. It was revealed that among 4328 hospitalized pediatric patients, a total number of 342 patients had one or more nosocomial infections, yielding 411 episodes. Twenty-five per cent of isolated S. aureus was resistant to either ampicillin or oxacyllin. Higher percentages of resistance were observed in S. albus, i.e., to penicillin (53.3%) and oxacyllin (46.7%), and to cefuroxime, erythromycin and clindamycin (each in 40.0% of isolate). E. coli was In 86.3% resistant-to ampicillin, 78.4% to chloramphenicol (and thiamphenicol), 56.8% to tobramycin and 48.2% to gentamicin. The isolated Salmonella sp was almost 100% resistant to ampicillin and chloramphenicol (and thiamphenicol) but was highly sensitive to amikacin, cefotaxime and netilmicin, arround 100%. Pseudomonas sp was 92.9% resistant to ampicillin, 85.7% to chloramphenicol (and thiamphenicol) and 78.6% to cefuroxime; on the contrary it was 92.9% sensitive to amikacin. It can be concluded that gram-negative microorganisms were in general showed highly resistant to ampicillin, chloramphenicol (and thiamphenicol), tobramycin, and gentamicin; on the other hand more than 90% were sensitive to netilmicin, cefotaxime and amikacin.